NEW RECORDS AND REDESCRIPTION OF LABIDOCERA ROTUNDA MORI, 1929 (COPEPODA, CALANOIDA, PONTELLIDAE) FROM SEBATIK ISLAND, NORTH KALIMANTAN, INDONESIA, WITH NOTES ON ITS SPECIES-GROUP - Mulyadi Mulyadi (Treubia, 2019)
During a plankton trip around Sebatik Island, North Kalimantan, a copepod Labidocera rotunda Mori, 1929 (Calanoida, Pontellidae) was collected for the first time in Indonesian waters. Both sexes are redescribed and compared to previous descriptions. The geographical distribution of the species confirms that it is of Indo-Pacific origin. There has been a mix-up between L. rotunda described by Mori (1929) from Pusan, Korea and L. bipinnata from Sagami Bay, described by Tanaka (1936). Fleminger et al. (1982) have argued that the minor difference is based on the presence or absence of cephalic hooks and had synonymized L. bipinnata with L. rotunda.